Structure of carbon black continuously produced from biomass pyrolysis oil. Issue 17 (2nd August 2018) - Toth, Pal; Vikström, Therese; Molinder, Roger; Wiinikka, Henrik
Abstract : Renewable-based carbon black was produced using pyrolysis oil derived from pine and spruce stem wood as feedstock in a continuous, high-temperature spray process. Abstract : Renewable-based carbon black was produced using pyrolysis oil derived from pine and spruce stem wood as feedstock in a continuous, high-temperature spray process. The particle size, micro- and nanostructure of the carbon black particles were investigated using High Resolution Transmission Electron Microscopy. The effect of process parameters on the structural properties of the product was studied. Conditions that yielded products structurally similar to commercial carbon black were identified. The results indicate that biomass pyrolysis oil can be used as a feedstock to produce renewable-based carbon black in a continuous process that is flexible and scalable. The structural properties of the products depended on process temperature and were consistent with those of commercial carbon black.